Model for Change: A Rural Elementary School - Gerald C. Ubben (Educational Considerations, 1975)
An unusual program in a small, rural school uses individualized instruction, student self-scheduling, freedom, an outdoor classroom, teachers-as-advisers, learning centers rather than classrooms, and a library which is the true heart of the school.